2020
DOI: 10.1017/s0016756820000783
|View full text |Cite
|
Sign up to set email alerts
|

Geochemistry and zircon ages of the Yushigou diabase in the Longshoushan area, Alxa Block: implications for crust–mantle interaction and tectonic evolution

Abstract: The North Qilian orogenic belt in North China has been defined as a subduction–collision zone between the Alxa Block and the Qilian Block. We present petrography, zircon U–Pb geochronology, major- and trace-element geochemistry, and Sr–Nd–Pb–Hf isotope analysis for the Yushigou diabase from the Longshoushan area, which is located SW of the Alxa Block, aiming to understand its petrogenetic link to subduction processes. The Yushigou diabase belongs to the tholeiite series, and shows enrichment in light rare eart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 79 publications
0
2
0
Order By: Relevance
“…The Lu-Hf and Sm-Nd isotopic systems have similar geochemical characteristics, and hence the εHf(t) and εNd(t) values show strongly positive correlation . Nd-Hf decoupling of magmatic rocks are commonly related to residual garnet or zircon enrichment in the magma source region (Patchett et al, 2004;Vervoort et al, 2000;Zeng et al, 2021a), and/or crustal assimilation (Patchett et al, 1984;Carpentier et al, 2009). From Figure 8B, it is shown that the Tongdeng samples .…”
Section: Crustal Assimilationmentioning
confidence: 99%
See 1 more Smart Citation
“…The Lu-Hf and Sm-Nd isotopic systems have similar geochemical characteristics, and hence the εHf(t) and εNd(t) values show strongly positive correlation . Nd-Hf decoupling of magmatic rocks are commonly related to residual garnet or zircon enrichment in the magma source region (Patchett et al, 2004;Vervoort et al, 2000;Zeng et al, 2021a), and/or crustal assimilation (Patchett et al, 1984;Carpentier et al, 2009). From Figure 8B, it is shown that the Tongdeng samples .…”
Section: Crustal Assimilationmentioning
confidence: 99%
“…FIGURE 8 | (A) ( 87 Sr/ 86 Sr) i -εNd(t) and (B) εHf(t)-εNd(t) (base map afterZeng et al, 2021a;Zeng et al, 2021b) diagrams for the Longlin basalt samples. MORB, mid-ocean-ridge basalt; EM I and EM II, enriched mantle; HIMU, LCC/MCC, middle to lower continental crust; UC, upper continental crust; IMM, Indian MORB; PMM, Pacific MORB.…”
mentioning
confidence: 99%